Relación entre motivación y resistencia al cambio en personas que trabajan en una empresa del sector público, en Bogotá (Colombia) (2009)
The main goal of the study was to find the relationship between motivation and resistance to change in workers of a public sector company in Bogotá, Colombia. The study made contributions to Industrial/Organizational Psychology with regards to these two variables, specifically Supervision, Participation, Belonging, Communication, Teamwork, Job content, Leadership, Internal motivational conditions, Change culture, Individual and Group level, Authority acceptance, Preferred means, Task dedication, Passive resistance, Expectation, among others. An action field for the Psychologist is confirmed upon finding that controlling work conditions (with regards to motivation and factors that create resistance to change) in order to achieve an optimal performance is vital, and the perspective of Organizational Psychology becomes widened, since the Psychologist is a potential agent of change.